KARAKTERISTIK FINISHING DAN SIFAT DASAR LANTAI BAMBU SEBAGAI PENGGANTI KAYU SOLID - Khairun Hidayat; Naresworo Nugroho; Dede Hermawan (BRIN Publishing, 2022)
Bamboo as a substitute for flooring raw materials is very potential to be developed because generally flooring is made of solidwood or other types of hardwood which have high quality but limited availability. Bamboo is chosen in the flooring industry, becauseof its distinctive and shiny pattern, and has a fairly high density. In this study, the flooring were made with various strips arrangementof horizontal (H), vertical (V), and combination (K) using Indonesian bamboo and coated with various number of water-basedfinishing layers (0, 3, 5). The bamboo flooring were tested referring to the ISO 21629-1 bamboo flooring for indoor use standardto evaluate the influence of the treatments on test results, and is expected to be able to provide recommendations for the preparationof SNI for bamboo flooring. The tests include the Modulus of Elasticity (MOE), Modulus of Rupture (MOR), stain resist,adhesion test, abrasion test, and hardness by pencil test. The result showed that the vertical arrangement formulation with threelayers of coating exhibite the best average score in this study with an MOE value of 162,603 kg/cm2, MOR 1,259.331 kg/cm2,adhesion test 2―4B, abrasion test 0.1149 g, and hardness by pencil test 2-4H compared to other formulations and teak flooringas a control. This bamboo product innovation is expected to be produced commercially and with good characteristics and can be usedas a reference standard in making Indonesian standart of bamboo flooring